Female participation in management positions in Chilean sports organizations from a gender perspective - Matus-Castillo, Carlos; Serra, Pedrona; Soler, Susanna; Cornejo-Améstica, Miguel; Hinojosa-Alcalde, Ingrid (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
Gender policies in sports aim to promote the presence of women in management positions in sports organizations. In this context, from the data of three wide surveys conducted in Chile during the last decade, this article had two objectives: to compare the presence of women and men in boards of directions in different types of sports organizations; and to analyze differences in profiles between women and men in high-responsibility positions in each organization. The results showed a significant under-representation of women in management and leadership positions. The study found that Chilean sports organizations are vertically segregated, with a few having a balance between women and men, so despite the incorporation of women on boards of directors, there is still male predominance. The research highlights the need for measures for an effective application of gender policies in sports.